Analisis Efesiensi dan Efektivitas Pengelolaan Keuangan Daerah Pemerintah Provinsi Jambi - Fathiyah Fathiyah (Universitas Batanghari Jambi, 2020)
The purpose of this study is to analyze the level of efficiency and effectiveness of regional financial management of the Provincial Government of Jambi. The analytical tool used in this study is the analysis of efficiency ratios and effectiveness ratios with research data in the form of secondary data derived from the Jambi Provincial Government Budget Realization Report for 2015-2019. Then the results of the study are given an assessment based on the criteria listed in the Decree of the Minister of Home Affairs No. 690,900,327 of 1996. The conclusion from the results of this study is that based on the calculation results obtained that during the last 5 years the level of efficiency of the regional financial management of the Jambi Provincial Government fluctuated with an average level of efficiency of 96.90% and in the criteria of less efficient, whereas for the level of effectiveness it was an average of 98.45% in the effective criteria, but in the last 2 years the effectiveness continues to increase in the highly effective criteria.